Adipocyte OGT governs diet-induced hyperphagia and obesity. Issue 1 (December 2018) - Li, Min-Dian; Vera, Nicholas; Yang, Yunfan; Zhang, Bichen; Ni, Weiming; Ziso-Qejvanaj, Enida; Ding, Sheng; Zhang, Kaisi; Yin, Ruonan; Wang, Simeng; Zhou, Xu; Fang, Ethan; et al.
Abstract Palatable foods (fat and sweet) induce hyperphagia, and facilitate the development of obesity. Whether and how overnutrition increases appetite through the adipose-to-brain axis is unclear.O -linked beta-D-N -acetylglucosamine (O-GlcNAc) transferase (OGT) couples nutrient cues to O-GlcNAcylation of intracellular proteins at serine/threonine residues. Chronic dysregulation of O-GlcNAc signaling contributes to metabolic diseases. Here we show that adipocyte OGT is essential for high fat diet-induced hyperphagia, but is dispensable for baseline food intake. Adipocyte OGT stimulates hyperphagia by transcriptional activation of de novo lipid desaturation and accumulation of N-arachidonyl ethanolamine (AEA), an endogenous appetite-inducing cannabinoid (CB). Pharmacological manipulation of peripheral CB1 signaling regulates hyperphagia in an adipocyte OGT-dependent manner. These findings define adipocyte OGT as a fat sensor that regulates peripheral lipid signals, and uncover an unexpected adipose-to-brain axis to induce hyperphagia and obesity. Endocannabinoid signaling regulates food intake and is a potential therapeutic target for obesity. Here the authors show that adipocyte O-GlcNAc transferase (OGT) is required for high fat diet-induced hyperphagia via transcriptional activation of de novo lipid desaturation and accumulation of an endogenous appetite-inducing cannabinoid.